INVESTIGATING THE POTENTIAL GENETIC ASSOCIATION OF SALIVARY AND TONGUE MICROBIOTA WITH PERIODONTITIS: A MENDELIAN RANDOMIZATION STUDY (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Chronic periodontitis (CP) is characterized by subgingival microbial dysbiosis and demonstrates distinct microbial profiles; however, clear causal relationships with microbiomes from separate oral regions remain poorly defined. Genome-wide association study (GWAS) data for CP and oral microbial communities were obtained from a large European cohort and the China National GeneBank DataBase (CNGBdb), respectively. Using single-nucleotide polymorphisms (SNPs) as genetic instruments, Mendelian randomization (MR) analyses were performed via the inverse-variance weighted (IVW) method. Analytical procedures were executed using the ‘TwoSampleMR’ package (version 0.6.4) in R. Sensitivity analyses were conducted to confirm result robustness and limit horizontal pleiotropy.
Keywords: Mendelian randomization, Oral microbiome, Periodontitis, Tongue microbiota.